Smart phones support smart labor - Michael Hübler; Rebecca Hartje (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2015)
Besides enabling communication, mobile phones and smartphones support information flows and financial transactions, especially in developing countries, where the coverage of landline networks is limited. Drawing upon new data from rural households in Southeast Asia, this paper shows that mobile phone or smartphone ownership supports local employment and commuting while it reduces incentives for migration of workers.
Keywords: J61; O33; O53; R11; 330; smartphones; mobile phones; labor markets; labor mobility; economic development; Southeast Asia